Sumbangan Imam Al-Nawawi Kepada ’Ulum Al-Hadith (Dirayat) - Abd. Rahman, Mohd. Muhiden (Jurnal Usuluddin, 1996)
Imam al-Nawawi was an eminent ulama’ in the 7H. He was well known as a specialist in fiqh and hadith. Nevertheless, his immense works in fiqh made him a well-known ulama’ rather than a muhaddith. However, an investigation on his works of hadith showed that he was among the famous muhaddithun. In fact, he could even be placed on par with other prominent muhaddithun such as al-Hakim, Ibn al-Salah, al-Tirmidhi, Abu Dawud and others. Therefore this article focuces his works in hadith dirayat or mustalah al-Hadith.